Calvino, Cerrone, and the Catacoustic: An "Echo-logical" Reading1. (3rd July 2021) - Rushing, Robert
Abstract : Catacoustics (an ancient term for the science of reflected sound, briefly championed by Lacoue-Labarthe) in fact tells us that the echo is never a partial and degraded repetition: while it is true that an echo repeats only a portion of the original signal, it does so in a way that also conveys a huge quantity of additional information that was not in the original signal—information that effectively describes the larger space in which the sound reverberates. In short, a catacoustic approach suggests that it is only in and with the echo that the sound is fully realized, and this realization or repletion of the origin happens in a way that demarcates and defines a space—something the mirror image does not gesture at. In this essay, I "listen by echo" in order to elaborate an "echo-logical" reading of Calvino's Invisible Cities, and Christopher Cerrone's opera of the novel, an opera that not only reflects on the question of reverberation and echo, but that also prolongs, amplifies and enriches Calvino's original work, helping us to better discern both artists' commitment to improving our political spaces and ecologies.